Liver resection after selective internal radiotherapy (SIRT): Proof of concept, initial survival, and safety. Issue 4 (8th August 2015) - Justinger, Christoph; Kouladouros, Konstantinos; Gärtner, Daniel; Tatsch, Klaus; Reimer, Peter; Rüdiger, Thomas; Binnenhei, Martin; Bentz, Martin; Schön, Michael R.
<x xml:space="preserve">Abstract</x> Background and Objectives Extent of liver resections are restricted by the volume of the future liver remnant. Different strategies have been developed to increase the frequency of curative resections. Selective internal radiation therapy (SIRT) has emerged as an effective therapy for patients with primary non‐resectable malignancies of the liver. Here, we report the first clinical series of patients with curative liver resection following SIRT. Methods Starting 2010, patients with marginally resectable liver metastases treated by SIRT followed by liver resection were identified and prospectively documented in a database for subsequent retrospective analysis. Results Thirteen patients (five female, eight male; age 70 years [32–77 years]) with marginally resectable liver metastases were selected for liver resection after SIRT. After performing SIRT, 12 patients had potentially curative hepatic resection. In two patients, liver resection after SIRT could not be performed due to the appearance of new extrahepatic metastases. Analyzing the effect of SIRT, we observed a decrease in tumor size with central scaring. None of the patients developed liver necrosis after SIRT. Liver resection was performed safely in all patients. Conclusions The combination of SIRT with state‐of‐the‐art liver surgery opens up new therapeutic options in patients with liver metastases. J. Surg. Oncol. 2015; 112:436–442. © 2015 Wiley Periodicals, Inc.